Industrial manufacturing linked to the mechanical and economic viewpoint of the mold steel grinding process using aluminum oxide wheel - Moretti, Guilherme Bressan [UNESP]; Ávila, Benício Nacif [UNESP]; Lopes, José Claudio [UNESP]; de Moraes, Douglas Lyra [UNESP]; Garcia, Mateus Vinicius [UNESP]; Ribeiro, Fernando Sabino Fonteque; de Mello, Hamilton José [UNESP]; Sanchez, Luiz Eduardo De Angelo [UNESP]; Aguiar, Paulo Roberto [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Springer Nature, 2021)
During the grinding process, cutting fluids are essential to guarantee the surface quality of the workpieces. On the other hand, these fluids can also compromise the efficiency of the process to view the alignment of economic and socio-environmental issues. Currently, the flood lubrication method is the most used. However, the minimum quantity lubrication (MQL) technique is an excellent alternative to use due to the negative aspects of the flood. Thus, this article compares the performance of the MQL technique with the flood method in the cylindrical grinding of steel for VP50 mold. The grinding wheel used was aluminum oxide and three feed rates (0.25, 0.50, and 0.75 mm/min). The results were obtained from analysis of output parameters: surface roughness (Ra), roundness error, G-ratio, scanning electron microscopy, specific grinding energy, microhardness, metallography, cost, and pollution analyses. The surface roughness obtained with MQL (0.72 μm) was only 13% higher than the flood method (0.64 μm) for a feed rate of 0.25 mm/min. Also, MQL reduced the costs of grinding and CO2 emissions by 200% and 210% compared to the flood, respectively. Therefore, these results show that the MQL technique combined with a low feed rate is a good alternative for lubrication and cooling since it presents values significantly close to the conventional cutting fluid, in addition to the lower costs and socio-environmental impacts generated.
Keywords: Aluminum oxide wheel; Cutting fluid; Flood; Grinding; Mold steel; MQL